THE IMPLEMENTATION OF PEOPLE PARTICIPATION PRINCIPLE IN PROTECTION AND MANAGEMENT OF THE ENVIRONMENT ON ROCK QUARRY EFFORT IN DONGGALA REGENCY - Hidayatullah, Syarif (Universitas Tadulako, 2018)
This writing intends to know the application of the principle of community participation in environmental protection and management of rock mining in Donggala Regency and supporting factors of community participation in environmental protection and management of the rock mining business. Through empirical legal research methods, The data analysis used is qualitative. The results of this study indicate that: first, the principle of community participation in environmental protection and management of rock mining in Donggala Regency is still low. And secondly, the supporting factor of community participation in the protection and environmental management of the rock mining business in Donggala regency is local government, non-governmental organizations, community education and facilities / infrastructure.